Canadian private protected areas are located in regions of higher vertebrate species richness than government protected areas - Leonardo B. Custode; Matthew M. Guzzo; Natasha Bush; Claire Ewing; Michael Procko; Samantha M. Knight; Marie-Michele Ro; D. Ryan Norris (Canadian Science Publishing, 2021)
Nongovernmental organizations contribute to the securement and management of protected areas, but it is not well known how their lands compare to government protected areas or the effectiveness of different land acquisition strategies. Using data from the International Union for Conservation of Nature and BirdLife International, we estimated total and at-risk terrestrial native vertebrate species richness in southern Canada among (i) private protected areas secured by the Nature Conservancy of Canada (NCC), government protected areas, and randomly sampled land; (ii) conservation agreements and fee simple (directly acquired) NCC properties; and (iii) purchased or donated fee simple properties. Controlling for property size and ecoregion, NCC protected areas were predicted to be in areas with 6% and 13% more total and at-risk species than randomly sampled land and 4% and 6% more total and at-risk species than government protected areas. Within NCC protected areas, conservation agreements were predicted to be in areas with 2% and 4% more total and at-risk species than fee simple properties, but purchased properties had similar numbers of total and at-risk species as donated properties. Although we caution that diversity estimates were based on course-grained range maps, our findings suggest that private protected areas are important in conserving biodiversity.